A sanção tributária e a consensualidade - Col, Alessandro Del (2023)
The present work aims to carry out the construction of a logical-syntactic, semantic and pragmatic meaning of the tax sanction, delimiting the object without communication noises, eliminating or reducing the ambiguities that the linguistic term has. And undertake a theoretical framework of the consensus incident on the sanctioning prerogative of the Sanctioning Tax Law. In the first part, the digression on the Theory of Logical-Semantic Constructivism was adopted as a theoretical-hermeneutic framework that projects a methodological framework for the construction of legal and tax sanctions. For the construction of the tax sanction, a syntactic analysis of the sanctioning legal norm based on the Logic of Law is carried out, and a matrixrule of sanctioning incidence with doctrinal influences is proposed. In the construction of the sanction in its semantic and pragmatic aspects, we went through the verification of the functions of legal and tax sanctions to direct a functionality and rationality that they can exercise in the protection of the legal order, and the measurement of illegality as a presupposition of normative validity. Then, the classification of tax sanctions into punitive pecuniary sanctions and interventional non-pecuniary sanctions was carried out, by methodological cuts, for the understanding of these objects for the verification of the consensual models to be developed within the Sanctioning Tax Law. In the second stage of this study, the theoretical foundations for the consensus of the tax sanction were presented as a tool available to the Tax Administration to confer a rationality of the sanctioning power and extract a functionality aligned with its normative function. As a theoretical framework in the evolution of Sanctioning Administrative Law, the new paradigms for the construction of a Democratic State of Law and for consensual Public Administration and the constitutional foundations that marked this hermeneutic mutation as an inexhaustible source of interpretative axiom were analyzed. Thus, the consensuality in Sanctioning Tax Law is investigated as an alternative way to the traditional method of conflict resolution, carrying out a theoretical deepening in the expansion of consensuality on sanctioning prerogatives. For this, we carried out an investigation on the existing models in Comparative Law and the current stage of potentially conciliatory instruments existing in the Tax Law that have or not a focus on the sanctioning power, and highlighted some instruments that have compatibility to print concerted acts on the sanctioning power. taxation, giving greater effectiveness to the sanctioning legal norm and strengthening its functionality. We adopt the analytical-hermeneutic and dogmatic analytical and normative method